Important Factors in the Formation of Spiritual and Moral Education Through Physical Training and Sports - Yusupov Akmaljon Abdug’opporovich; Xamraliev Murodil Maxammadjonovich (Genius Journals, 2022)
The article discusses the need to understand the human culture in an educational process and a complete understanding of the issues of spirituality and ideology that play an important role in the younger generation. The content of the article is based on the idea that the understanding of the nature of man and the formation of spirituality in it is the basis of the work of teachers and educators.
Keywords: The world; intangible element; man; spirituality